Effectiveness of the management development programs of the Central Bank of the Philippines - Rissal, Romeo (1983)
The subjects are 370 middle executives who provided data about executive job behavior through two sets of questionnaires, one of which the executives answered to evaluate themselves, and the other answered by their respective superiors, peers and subordinates to evaluate them. The executives' work performance under the Performance Appraisal System were analyzed using the stepwise regression analysis. The Executive Development Course and the Seminar on Effective Communication are effective in bringing about favorable changes in the executives' job behavior and work performance. Both courses have a very significant joint effect on the executives' job behavior and work experience.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Diliman.
Keywords: Central Bank of the Philippines -- Officials and employees; Executives -- Training -- Philippines; Manila